Fungsi Reog Singo Wogro Dalam Suronan Di Desa Maitan Kabupaten Pati - Yheni Aprilia Susanti; Mamik Widyastuti (Jurnal Sitakara, 2023)
The aim of  this study discuss the function of Reog Singo Wogro in the Suronan Ritual of Maitan village, Pati regency, took two problems. The first talking about what is the form of Reog Singo Wogro in the Suronan ritual of Maitan village, Pati regency. The second talking about how is the function of Reog Singo Wogro in the Suronan ritual in Maitan village, Pati regency. The problems were analyzed by using theory of form from Sri Rochana and the theory of function uses theory of Soedarsono. This study uses qualitative data, the data of study were obtained through observation, interview, and literature review. The result of study shows that: Reog Singo Wogro consists of five parts, they  are chanting mantras, Barongan dance, Jaranan dance, Gambyongan dance, and Bendrong. The form includes the structure and elements. Reog Singo Wogro has a function as a means of ritual, as a means of personal entertainment, and as an aesthetic presentation or spectacle that affects Maitan villager. Keyword: Reog Singo Wogro, form, function